Low-Dose Adefovir Dipivoxil May Induce Fanconi Syndrome: Clinical Characteristics and Long-Term follow-up for Chinese Patients. Issue 6 (August 2015) - Xu, Li-Jun; Jiang, Yan; Liao, Ruo-Xi; Zhang, Hua-Bing; Mao, Jiang-Feng; Chi, Yue; Li, Mei; Wang, Ou; Liu, Xiao-Qing; Liu, Zheng-Yin; Xing, Xiao-Ping; Yu, Wei; et al.
Background: Adefovir dipivoxil (ADV) nephrotoxicity is well known at a dose of 60 mg day -1 or 120 mg day -1 . However, renal toxicity at a low-dose of 10 mg ADV for HBV-infected patients is not fully described. Our objective was to analyse the clinical features and outcomes of ADV-related Fanconi's syndrome in the Chinese population. Methods: This was a retrospective study. A total of 35 patients with ADV-related Fanconi's syndrome were studied. Clinical manifestations and biochemical parameters were analysed. 19 patients were from Peking Union Medical College Hospital (PUMCH) included from August 2010 to December 2012. A total of 16 patients were eligible from case reports in the Chinese population retrieved in PUBMED, WANFANG and CNKI database. Bone mineral density and biochemical parameters including serum phosphate, calcium, creatinine, alkaline phosphatase (ALP) were measured before and after ADV cessation and during the follow-up. Results: All recruited patients had hypophosphataemia, increased urinary phosphate excretion and elevated alkaline phosphatase. Serum phosphate levels rapidly increased especially within the 4 weeks after ADV cessation. Serum creatinine remained high or at the upper limit of normal range even after ADV cessation for 1 year. ALP increased in the first three months of ADV cessation and decreased at the 24th week. Bone mineral density was significantly improved after 6 months cessation of ADV. Conclusions: ADV can be nephrotoxic at prolonged low doses of 10 mg. For those who take ADV long term, regular monitoring of serum phosphate, creatinine levels and urine routine tests are required.